Recommendations for a standard UK approach to incorporating umbilical cord blood into clinical transplantation practice: an update on cord blood unit selection, donor selection algorithms and conditioning protocols. (18th November 2015) - Hough, Rachael; Danby, Robert; Russell, Nigel; Marks, David; Veys, Paul; Shaw, Bronwen; Wynn, Rob; Vora, Ajay; Mackinnon, Stephen; Peggs, Karl S.; Crawley, Charles; Craddock, Charlie; et al.
Summary: Allogeneic haemopoietic stem cell transplantation offers a potentially curative treatment option for a wide range of life‐threatening malignant and non‐malignant disorders of the bone marrow and immune system in patients of all ages. With rapidly emerging advances in the use of alternative donors, such as mismatched unrelated, cord blood and haploidentical donors, it is now possible to find a potential donor for almost all patients in whom an allograft is indicated. Therefore, for any specific patient, the transplant physician may be faced with a myriad of potential choices, including decisions concerning which donor to prioritize where there is more than one, the optimal selection of specific umbilical cord blood units and which conditioning and graft‐ versus ‐host disease prophylactic schedule to use. Donor choice may be further complicated by other important factors, such as urgency of transplant, the presence of alloantibodies, the disease status (homozygosity or heterozygosity) of sibling donors affected by inherited disorders and the cytomegalovirus serostatus of patient and donor. We report UK consensus guidelines on the selection of umbilical cord blood units, the hierarchy of donor selection and the preferred conditioning regimens for umbilical cord blood transplantation, with a summary of rationale supporting these recommendations.